Report of the Scottish Departmental Committee on the North Sea Fishing Industry : report , part 1 - Conacher, H.M.; Moffat, J. (London: Scottish Departmental Committee on the North Sea Fishing Industry, 1914)
"H.M. Conacher Bibliotheek E. Anseele"